Grevillea pteridifolia (SYN. Grevillea banksII)-a Successful Introduction to Mined out Areas of Madhya Pradesh-I - Prasad, Ram; Chadhar, S. K. (Indian Forester, 1987)
Large tracts of rich forests are being cleared for mining in Madhya Pradesh. After mining the areas are rendered wastelands where site conditions become Inhospitable for normal plant growth. However, State Forest Research Institute, M.P., Jabalpur has got Success in evolving metbodologies for the rehabilitation and revegelation of such mined out sites. Out of the seven most successful species on the mined out areas of bauxite, an Australian species Grevlllea pleridifolia has been found most promising. This species having adopted to the site has been found to be the best producer of organic matter, Natural regeneration of this species have also been observed. This species has been fouod successful at other mined out sites (coal and dolomite) also. Botanical characteristics of this species have been described in this paper.